REDISAIN SISTEM PEMBUMIAN DI HOTEL X JIMBARAN - Khana Eland N.A; I.G.N Janardana; I.W Arta Wijaya (Jurnal SPEKTRUM, 2021)
Due increases develop the electric power system, the more effective security system is needed.One of the security systems is the earthing system at Hotel X Jimbaran. After takes measurement theaverage measurement results of 1.14 ? ~ 2.47 ? at four different location points that cause the flow ofovercurrent or overvoltage to electrical equipment. This study purpose to improve the existing earthingsystem to achieve earthing resistance <1? according to IEEE standards.This research method consist ofseveral stages, first, survey location to measure the amount of soil resistance (R) to calculate the value ofsoil resistivity (?) then calculate the value of earthing resistance according to the type of earthing systemto achieve an earthing resistance <1 ?, including the Vertical One Earthing Electrode System at Depth Z,Horizontal Earthing One Electrode System, Two Earthing Electrode System with S>L conditions, TwoEarthing Electrode Earthing System with S<L conditions, Plate Earthing System and Grid-Rod EarthingSystem.The calculation analysis results design of the earthing system with earthing resistance <1? each fault location obtained different results. Building 1000 reccomended to choose plate earthing system inwetsoil conditions with the result of earthing resistance 0,9594?; Building 2000 reccomended to choose gridrod earthing system in dry soil conditions with the result of earthing resistance 0,84?; Building 3000reccomended to choose grid-rod earthing system in dry soil conditions with the result of earthingresistance 0,976?; and Ballroom reccomended to choose grid-rod earthing system in wet soil conditionswith the resultof earthing resistance 0,865?. Each location according to the analyzed earthing systemrecommendations, the most economical prices were calculated below IDR 10,000,000,- (Ten MillionIndonesia Rupiah Currency), at Building 1000 with a total cost of IDR.4.034.000,-; Building 2000 with atotal cost of IDR.6.698.650,-; Building 3000 with a total cost of IDR.7.448.200,-; and Ballroom with a totalcost of IDR.7.352.200,-.